Structural Analysis of The Values Contained in Sang Pemimpi Novel by Andrea Hirata - Roza Khairani; Marudut Bernadtua Simanjuntak (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2022)
Literature has a great interest in various circles. Likewise with novels that have various useful values. Sang Pemimpi novel by Andrea Hirata is the second book in the Laskar Pelangi novel tetralogy. Novels are in great demand in various circles, this is evidenced by the novel Sang Pemimpi which was able to win a Mega Best Seller. In the novel, Sang Pemimpi tells the story of three young men, namely Ikal, Arai, and Jimbrong. This novel also tells about friendship and the many values it contains. The study in this paper aims to be able to analyze, identify and describe systematically the values contained in the novel Sang Pemimpi. Therefore, this research will review from various value perspectives. The research method uses a descriptive-qualitative method or also known as the exposure method, which is a method to produce information about the message or values contained in the novel which will be carried out with analytical techniques. The data collection technique used is the reading and note-taking technique. The results of the study will explain or provide an overview of the values of life contained in the novel Sang Pemimpi by Andrea Hirata.